Vascular Tissue-Type Plasminogen Activator Promotes Intracranial Aneurysm Formation. Issue 9 (September 2017) - Labeyrie, Paul-Emile; Goulay, Romain; Martinez de Lizarrondo, Sara; Hébert, Marie; Gauberti, Maxime; Maubert, Eric; Delaunay, Barbara; Gory, Benjamin; Signorelli, Francesco; Turjman, Francis; Touzé, Emmanuel; Courthéoux, Patrick; et al.
Abstract : Background and Purpose—: Although the mechanisms that contribute to intracranial aneurysm (IA) formation and rupture are not totally elucidated, inflammation and matrix remodeling are incriminated. Because tPA (tissue-type plasminogen activator) controls both inflammatory and matrix remodeling processes, we hypothesized that tPA could be involved in the pathophysiology of IA. Methods—: Immunofluorescence analyses of tPA and its main substrate within the aneurysmal wall of murine and human samples were performed. We then compared the formation and rupture of IAs in wild-type, tPA-deficient and type 1 plasminogen activator inhibitor–deficient mice subjected to a model of elastase-induced IA. The specific contribution of vascular versus global tPA was investigated by performing hepatic hydrodynamic transfection of a cDNA encoding for tPA in tPA-deficient mice. The formation and rupture of IAs were monitored by magnetic resonance imaging tracking for 28 days. Results—: Immunofluorescence revealed increased expression of tPA within the aneurysmal wall. The number of aneurysms and their symptomatic ruptures were significantly lower in tPA-deficient than in wild-type mice. Conversely, they were higher in plasminogen activator inhibitor–deficient mice. The wild-type phenotype could be restored in tPA-deficient mice by selectively increasing circulating levels of tPA via hepatic hydrodynamic transfection of a cDNA encoding for tPA. Conclusions—: Altogether, this preclinical study demonstrates that the tPA present in the blood stream is a key player of the formation of IAs. Thus, tPA should be considered as a possible new target for the prevention of IAs formation and rupture. Abstract : Supplemental Digital Content is available in the text.